Coping with low moisture stress: Remembering and responding. Issue 2 (25th February 2021) - Choudhary, Mukesh; Singh, Alla; Rakshit, Sujay
Abstract: Low‐moisture stress, also referred to as drought, is one of the major factors that negatively impact the agricultural yield. The present scenario of climate change is expected to aggravate it further. Considering the extended time required to develop resistant crops, it is important to prioritize research efforts for coping with low moisture, prevalent in arid and semi‐arid regions of the world. While agricultural yield is a tradeoff between many choices, tolerance to biotic and abiotic stresses comes with yield penalties. To balance the tradeoffs and maximize productivity, the use of region‐specific cultivars and/or introgression of precise genetic proportions in an elite variety may prove useful. Stress memory is an emerging approach that helps plants to record and respond to repeated stress in an effective manner. In this context, we discuss the role of "stress memory" in imparting drought tolerance in plants. Future research efforts for its effective deployment for "drought hardening" in agricultural settings, along with a discussion on the yield tradeoff involved, is implicated.